Strontium-substituted calcium sulfate hemihydrate/hydroxyapatite scaffold enhances bone regeneration by recruiting bone mesenchymal stromal cells. (July 2020) - Chang, Hong; Xiang, Haibo; Yao, Zilong; Yang, Shenyu; Tu, Mei; Zhang, Xianrong; Yu, Bin
Fabrication of osteoconductive scaffold with osteoinductive capability and appropriate resorption rate is of great significance for treating bone defects. To achieve this aim, strontium-substituted calcium sulfate hemihydrate (Sr-CSH) and hydroxyapatite (HA) were mixed to develop a novel composite. Sr-CSH containing 5% and 10% strontium was mixed with HA at the weight ratio of 6:4, respectively. Female Sprague-Dawley rats underwent bone defect surgery in left tibia were randomly assigned to three different treatment groups filled with CSH/HA, 5% and 10% Sr-CSH/HA. Micro-CT analysis showed increased new bone formation in 10% Sr-CSH/HA group compared to CSH/HA group. In addition, histological analysis showed large amounts of chondrocytes and osteoblasts within the pores of Sr-CSH/HA composites as a result of the CSH resorption. Further, CFU-F assay demonstrated the increased amount of bone marrow mesenchymal stromal cells (BMSCs) colonies in 10% Sr-CSH/HA group. In primary BMSCs, extraction from Sr-CSH/HA composite significantly increased the migration of cells, up-regulated the expression of osteoblastic marker genes, and increased the area of mineralized nodules. Together, Sr-CSH/HA may promote bone formation by recruiting and stimulating osteogenic differentiation of BMSCs. Therefore, this composite may be proposed as an ideal substitute to repair bone defects.